INDIKATOR KINERJA UTAMA JENJANG PENDIDIKAN SEKOLAH MENENGAH SEDERAJAT DI INDONESIA: SUATU STUDI LITERATUR - Muh. Bukhari; Ryan Saputra Alam; Hurian Kamela (Scientia Integritas Utama, 2022)
There must be indicators of education-based activities, especially in secondary schools. The aim is to analyze the indicators of high school in Indonesia qualitatively. The research uses a qualitative literature study with data on comparisons of secondary schools so that they can be mutually based on previous literature. The primary data that are compared qualitatively are (1) Comparison of secondary schools, a study on the performance of the Provincial Education Office, and (2) Application of a performance-based reward system in High Schools and Equivalent. As a result, the performance of the Provincial Education Office tends to focus on only 2, namely (1) increasing access, equitable distribution of quality education for secondary and special schools, and (2) improving the qualifications, competence of educators, and education personnel for secondary and special education.